A complete tattoo-based wireless biofuel cell using lactate directly from sweat as fuel. (November 2019) - Escalona-Villalpando, R.A.; Ortiz-Ortega, E.; Bocanegra-Ugalde, J. P.; Minteer, S. D.; Arriaga, L.G.; Ledesma-García, J.
Abstract: In this work, an enzymatic type wireless biofuel cell (BFC) has been implemented. The bioanode consisted in the immobilization of the enzyme lactate oxidase (LOx) with the dimethylferrocene-modified redox polymer linear polyethylenimine LPEI (FcM2 -LPEI) and 5 % EDGE at a volumetric ratio of 56/24/3 and thoroughly mixed. The biocathodes were prepared immobilizing bilirubin oxidase (BOx) mixed with 7.5 mg of multi-walled carbon nanotubes MWCNT modified with anthracene and TBAB-Nafion by successive vortex mixing/sonication steps and the paste was deposited qualitatively on flexible Toray carbon (TC-PTFE) using a brush. The cyclic voltammetry results of the bioanode and biocathode show an enzymatic activity in the lactate oxidation and oxygen reduction reactions in PBS and human sweat respectively. The evaluation of BFC tattoo was performed in different parts of the body under conditions of exercise by a healthy volunteer, finding that located on the chest, was obtained the greatest current (96 μA) with 0.55 V of OCP monitoring the system using a potentiostat and a wireless controlled device.